A Website Designed to Relieve People’s Depression - Zhou, Chuhao (Transactions on Computer Science and Intelligent Systems Research, 2024)
With time going by, depression is getting more and more concern from society. With depression, they don’t have stable emotions, which leads to a problem that they tend to feel hopeless and sometimes even drop into despair when they’re viewing webs. Apart from that, there’re also lots of people with depression teies. And lots of people are still suffering from the pain of the disease and the effects of depression.Therefore, This study is aimed to design a website for those people with depression and those potential people, aimed to decrease the risk of their getting into disease. My target is to build a healthy and positive online environment, which is beneficial for their mental health. And to research and conclude a series of principle and regulations of the relevant website designing. During the research, the method of issuing questionnaires is adopted, and a lot of websites like CNKI and Web of Science were referred to learn articles published between 2000 and 2024 related to the depressive symptoms and webpage design. A proper website for the specific group has been created, and meanwhile, lots of practical advice are summarized on how to design similar websites. Eventually, hope the work can make an influence to the future research and design in relevant areas.